Avaliação de três formas de enriquecimento em área ciliar revegetada junto ao Rio Mogi-Guaçu, SP - Aquino, Clarissa de [UNESP] (2006)
The present work is a result of a partnership between the Secretaria Estadual do Meio Ambiente and the International Paper do Brasil. lts aim was to attend to projects regarding lhe preservation and recovery of riparian forests at Mogi-Guaçu region. The goal was to evaluate different alternatives (leaf iitter and rain seed) for the enrichment of the riparian forest implemented in 1996 at the company domam. Besides, there was an evaluation of lhe use of stored seeds and the control of germination in greenhouse, as comparative parameters. The study areas were: (a) Fazenda Ouro Verde (Conchal, SP), with reminiscent vegetation classified and a mesofila semidecidua riparian forest, with fluvial seasonal influence, where was conducted the gathering of leaf litter using mobile parcels of 1m2, and rain seed using 40 coilector with a nylon fence of 1 m2, arranged in 5 transects perpendicular to lhe Mogi-Guaçu river; (b) Parque Florestal São Marcelo (Mogi-Guaçu, SP), where was conducted the test of enrichment, mn sub-parcels of 2mx2m, distributed in 4 experimental sets of 25mx25m, in a revegetated riparian area with arboreal native species. There was no statistical difference for the mean number of species within the experimental treatments. The mean number of germinated individuais by the rain seed treatment was significantly higher than the leaf litter treatment. In general, the species that obtain lhe highest survival success along the experiment was Syagrus romanzoffiana Uerivá), Nectandra megapotamica (canela amarela), Eugenia brasillensis (grumixama) e Pseudobombax sp. (embiruçu), what corroborates lhe idea that the direct seeding of arboreal secondary species in revegetated areas can produce promissing results relating lhe germination and establishment of those species, specially understory conditions, contributing to the increase of local diversity. The general results showed that this... (Complete abstract, click electronic address below).